XXI IOSTE 2024: Science and Technology Education for Sustainability and Social Justice e-proceedings / Margaret Chan Kit Yok ... [et al.] - Chan, Margaret Kit Yok; Boiselle, Laila; Baptista, Monica; Arroio, Agnaldo; Engkamat, Adeline; Halamy, Suhaida (2025)
The XXI International Organisation for Science and Technology Education (IOSTE) 2024, held in Kuching, Sarawak, Malaysia, focuses on the theme "Science and Technology Education for Sustainability and Social Justice." This symposium addresses the urgent challenge that science education faces in keeping pace with global crises like climate change and the critical need for a STEM-educated workforce. It brings together researchers, policymakers, lecturers, and teachers to explore how STEM can contribute to the IOSTE mission. A key feature of the symposium is a Roundtable Discussion titled “Is STEM really too hard?”, directly engaging with the challenges and perceptions of STEM education in addressing these global issues.